2016
DOI: 10.1021/acs.jpcb.6b03779
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Molecular Dynamics Simulations of DNA–Polycation Complexes: Two Distinct Binding Patterns

Abstract: Synthetic cationic polymers represent a promising class of delivery vectors for gene therapy. Here, we employ atomistic molecular dynamics simulations to gain insight into the structure and properties of complexes of DNA with four linear polycations: polyethylenimine (PEI), poly-l-lysine (PLL), polyvinylamine (PVA), and polyallylamine (PAA). These polycations differ in their polymer geometries, protonation states, and hydrophobicities of their backbone chains. Overall, our results demonstrate for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
4
37
0
2
Order By: Relevance
“…For this, we employed B3LYP density functional theory 50 with the 6-31G* basis set, followed by the restrained electrostatic potential (RESP) 51 charge fitting using AmberTools. 52 Further investigations revealed that the values obtained are in a good agreement with the partial charges calculated by Kondinskaia et al 53 using a similar methodology. Therefore, for the protonated systems (P20 and P50), rather than performing DFT studies ourselves, we adopted the partial charges provided by Kondinskaia et al 53 Additional details about the model for partial charges and force field parameters can be found in the ESI.…”
Section: Force Field Parameterssupporting
confidence: 57%
“…For this, we employed B3LYP density functional theory 50 with the 6-31G* basis set, followed by the restrained electrostatic potential (RESP) 51 charge fitting using AmberTools. 52 Further investigations revealed that the values obtained are in a good agreement with the partial charges calculated by Kondinskaia et al 53 using a similar methodology. Therefore, for the protonated systems (P20 and P50), rather than performing DFT studies ourselves, we adopted the partial charges provided by Kondinskaia et al 53 Additional details about the model for partial charges and force field parameters can be found in the ESI.…”
Section: Force Field Parameterssupporting
confidence: 57%
“…The molecular dynamics (MD) studies of Choudhury et al on the solvation dynamics of linear PEI essentially employed the same Amber FF, without notable improvements. Equally starting from the Amber FF, the partial charges of PEI were derived in the studies of Kondinskaia et al from ab initio calculations on four model trimers by the RESP method.…”
Section: Introductionmentioning
confidence: 99%
“…REMD trajectory at 300K of each molecular system was analyzed to compute the RDF of the polycationic amine nitrogen atoms around O1P and O2P siRNA atoms ( Fig 4A ), in order to investigate the nature of the interactions between protonated amine groups and siRNA phosphate group oxygen atoms, as previously described [ 19 , 20 , 49 ]. The plots reported in Fig 4A are characterized by two different peaks at 2.7 Å and 4.3 Å, in agreement with previous computational observations [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been applied with success to address this issue, such as Metropolis Monte Carlo [ 42 44 ], enveloping distribution sampling [ 45 ], or λ-dynamics [ 46 48 ]. However, this work follows the common practice in molecular dynamics [ 19 21 , 49 , 50 ] by defining the protonation state at the beginning of the simulation. Further developments of this work may consider to explicitly focus on the dynamic protonation/deprotonation at constant pH in polymer/siRNA complexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation